Propagation of an Airy beam through atmospheric turbulence with optical vortex under fractional Fourier transforms. (November 2018) - Habibi, Forouzan; Moradi, Mohammad
Highlights: The AIB's characteristics are the effective beam size, number, width, height of spot and spot uniformity. The optical vortex destroys the spots uniformity of the AiB. The optical vortex position in the optical system changes for different powers of the FrFT. The image quality under the FrFT is improved compared with the FFT and for a specific atmospheric turbulence. Abstract: In this paper, we have theoretically investigated the behaviour of an Airy beam (AiB) with an optical vortex (OV) in atmospheric turbulence. The obtained splitting on each line of the phase pattern indicates the OV. The results show that the OV position changes when the power of the fractional Fourier transforms (FrFT) ( p ) changes. Moreover, uniformity of the spot beam disappears with the presence of the vortex in the AiB. The characteristics of an AiB, such as the effective beam size, number, width, height, and uniformity of the spot beam, change by changing the value of p . The position of the OV in the beam with scintillation and without scintillation was changed by changing the value of p .